The effect of multiple contacts between crack faces on crack contribution to the effective elastic properties. (15th May 2019) - Markov, A.; Abaimov, S.; Sevostianov, I.; Kachanov, M.; Kanaun, S.; Akhatov, I.
Abstract: The compliance contribution of a penny-shaped crack having multiple contacts between crack faces is analyzed. In order to reduce the number of parameters involved, regular lattices of circular contacts are considered. It is found, in particular, that, at the same total area of contacts, a large number of small contacts produces stronger stiffening effect than a small number of large contacts; hence the total contact area is not the parameter controlling the crack compliance contribution. The effects of contacts on both the normal and the shear crack compliances are found to be very close. In the case of moderately non-regular contact lattices, the results were found to be only marginally different from the results for regular ones. Results are conveniently expressed in terms of "Holm's radius"—the radius of a single contact that would have produced the same effect. Being applied to multiple cracks with contacts, our results yield the "adjusted", for the presence of contacts, value of crack density.